LEVELS OF REFLECTION IN EFL PRE-SERVICE TEACHERS’ TEACHING JOURNAL - Nurfaidah, Sitti; Lengkanawati, Nenden Sri; Sukyadi, Didi (Universitas Pendidikan Indonesia, 2017)
This article delineates a case study investigating the development of levels of reflection encapsulated in reflective teaching practice of four Indonesian EFL pre-service teachers during their field teaching. Data were garnered mainly through their reflective teaching journals and were analysed using thematic analysis technique to identify the emerging themes in level of reflection and to extract their narratives of experience. The findings indicated that regarding framework of level of reflection, the EFL pre-service teachers’ level of reflectivity is mostly in the range of dialogic reflection Level 3 and dialogic reflection Level 4. Within the range of dialogic reflection, the pre-service teachers revealed the ability to further describe, analyse and evaluate their instructional practices. No one, however, indicated the quality of critical reflection since it requires more experiences as invested in time and field teaching exposure.